2019
DOI: 10.3390/biom9060218
|View full text |Cite
|
Sign up to set email alerts
|

Albumin Nanovectors in Cancer Therapy and Imaging

Abstract: Albumin nanovectors represent one of the most promising carriers recently generated because of the cost-effectiveness of their fabrication, biocompatibility, safety, and versatility in delivering hydrophilic and hydrophobic therapeutics and diagnostic agents. In this review, we describe and discuss the recent advances in how this technology has been harnessed for drug delivery in cancer, evaluating the commonly used synthesis protocols and considering the key factors that determine the biological transport and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(65 citation statements)
references
References 149 publications
1
64
0
Order By: Relevance
“…Elevated gp60 and SPARC in the synovium fluid of RA patients and murine CIA model work to transports albumin across the endothelial barrier into the interstitium (Gp60) and SPARC enhances the uptake of albumin into immune cells in the RA synovium 24 , 26 . Albumin-based NPs can be taken up via the SPARC-mediated mechanism 60 and directly internalized by phagocytic cells via interactions with FcRn receptors, or after opsonization by IgG, and eventually sequestered within the endo-lysosomal compartment. The overall scheme of the NPs interactions and internalization within the RA site is presented in Figure 1 C .…”
Section: Resultsmentioning
confidence: 99%
“…Elevated gp60 and SPARC in the synovium fluid of RA patients and murine CIA model work to transports albumin across the endothelial barrier into the interstitium (Gp60) and SPARC enhances the uptake of albumin into immune cells in the RA synovium 24 , 26 . Albumin-based NPs can be taken up via the SPARC-mediated mechanism 60 and directly internalized by phagocytic cells via interactions with FcRn receptors, or after opsonization by IgG, and eventually sequestered within the endo-lysosomal compartment. The overall scheme of the NPs interactions and internalization within the RA site is presented in Figure 1 C .…”
Section: Resultsmentioning
confidence: 99%
“…As well known, SPARC, owing to its albumin binding properties, could promote the accumulation of albumin in cancer cells and tissues ( Tai and Tang, 2008 ; Bannunah et al, 2014 ; Bairagi et al, 2015 ; Cheng et al, 2017 ; Parodi et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Other types of detected modifications are questionable. It has been reported that phosphorylation of ALBU can occur non-specifically and, thus, create non-naturally originated identifications in proteomic assays [ 38 ]. On the other hand, enhanced non-specific phosphorylation of proteins, including ALBU in warfarin-binding site [ 39 ], is a known effect of the impaired cell signaling network, which significantly contributes in tumor growth and development [ 40 ].…”
Section: Resultsmentioning
confidence: 99%